Deterioro cognitivo y su influencia en la calidad de vida de los adultos mayores del cantón Saraguro, 2021 – 2022 - Álvarez Abad, Jessica Silvana (2022)
Cognitive impairment is a geriatric syndrome that occurs after 65 years of age, as a decline in cognitive functions, therefore the purpose of this research was to determine cognitive impairment and its influence on the quality of adults life of the Saraguro Canton, through a descriptive cross-sectional study with a quantitative and qualitative approach, applying a sociodemographic file, the Mini Mental State Test and the Gencat scale to a population of 90 seniors. It was determined that the majority of seniors present mild cognitive impairment, pathological suspicion and in a lower percentage dementia. Regarding to the quality of life, in the emotional well-being dimensions, interpersonal relationships, well-being material, physical well-being, self-determination, social inclusion and rights, most of them scoring positively in all dimensions, thus giving a result of a quality of life suitable. To establish the relationship between Cognitive Impairment and Quality of Life, the Chi-square statistical test was applied, where it was determined that there was no relationship between the two study variables